Suffering for territory : race, place, and power in Zimbabwe - Moore, Donald S., 1963- (e-Duke books scholarly collection., 2005)
An ethnographic study of Zimbabwe's land occupations that focuses on the effects of spatialized struggles on sovereignty and the nation-state.